2020
DOI: 10.1038/s41396-020-0682-7
|View full text |Cite
|
Sign up to set email alerts
|

Anthranilic acid from Ralstonia solanacearum plays dual roles in intraspecies signalling and inter-kingdom communication

Abstract: Quorum sensing (QS) signals are widely utilized by bacteria to regulate biological functions in response to cell population density. Previous studies have demonstrated that Ralstonia solanacearum employs two different types of QS systems. We report here that anthranilic acid controls important biological functions and the production of QS signals in R. solanacearum . It was demonstrated that the biosynthesis of anthranilic acid is mainly performed by TrpEG. The acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…Indole and anthranilate are important intermediates for the biosynthesis of alkaloid compounds. Although the absolute abundance and ecophysiological role of indole and its derivatives in methanogenic ecosystems, including our UASB reactor, remain unknown, previous studies reported that these compounds are associated with bacterial signaling in Escherichia coli and Ralstonia solanacearum ( Pinero-Fernandez et al , 2011 ; Song et al , 2020 ). PRPP may be further converted to His through a 10-step reaction employing ATP, Glu, and NAD + .…”
Section: Resultsmentioning
confidence: 99%
“…Indole and anthranilate are important intermediates for the biosynthesis of alkaloid compounds. Although the absolute abundance and ecophysiological role of indole and its derivatives in methanogenic ecosystems, including our UASB reactor, remain unknown, previous studies reported that these compounds are associated with bacterial signaling in Escherichia coli and Ralstonia solanacearum ( Pinero-Fernandez et al , 2011 ; Song et al , 2020 ). PRPP may be further converted to His through a 10-step reaction employing ATP, Glu, and NAD + .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that R. solanacearum uses two different types of QS systems: a phc QS system with 3-OH PAME and 3-OH MAME as signals and a typical lux QS system dependent on AHL signals. Our recent study identified a new signalling system, the anthranilic acid system, which controls important biological functions and the production of 3-OH MAME and AHL signals in R. solanacearum GMI1000 19 . In this study, we found that PutA positively controls the production of 3-OH MAME, AHL and anthranilic acid signals by directly controlling the transcriptional levels of the signal synthase-encoding genes by binding to the similar sequences in these promoters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli strains that can be used for general cloning and conjugal transfer were cultured in Luria-Bertani medium (10 g/L tryptone, 5 g/L yeast extract, 5 g/L NaCl; pH 7.0-7.5) or on LB agar (LB medium containing 15 g/L agar) at 37 °C. In the EPS quantitative experiment, SP medium (5 g/L peptone, 20 g/L glucose, 0.5 g/L KH 2 PO 4 and 0.25 g/L MgSO 4 ) was used to culture R. solanacearum 19 . All media were supplemented with antibiotics according to the experimental requirements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…at the root-microbiome interface can help shield the plant from pathogen infection [80,83,84]. Other mechanisms involved in the observed pathogen control might involve quorum sensing (QS) signals, siderophore-mediated interactions and systemically induced root exudation of metabolites (SIREM) [85][86][87]. Here, we report that the inoculation of speci c biological control agents can help stimulate speci c bene cial plant-associated microbes that together have the potential to protect the plants against pathogen attack.…”
Section: Impact Of Biocontrol Agent On the Resident Soil Community Asmentioning
confidence: 98%